Engaging and maintaining a sense of being informed: Understanding the tasks motivating twitter search. (7th May 2014) - Elsweiler, David; Harvey, Morgan
<x xml:space="preserve">Abstract</x> Micro‐blogging services such as Twitter represent constantly evolving, user‐generated sources of information. Previous studies show that users search such content regularly but are often dissatisfied with current search facilities. We argue that an enhanced understanding of the motivations for search would aid the design of improved search systems, better reflecting what people need. Building on previous research, we present qualitative analyses of two sources of data regarding how and why people search Twitter. The first, a diary study (p = 68), provides descriptions of Twitter information needs (n = 117) and important meta‐data from active study participants. The second data set was established by collecting first‐person descriptions of search behavior (n = 388) tweeted by twitter users themselves (p = 381) and complements the first data set by providing similar descriptions from a more plentiful source. The results of our analyses reveal numerous characteristics of Twitter search that differentiate it from more commonly studied search domains, such as web search. The findings also shed light on some of the difficulties users encounter. By highlighting examples that go beyond those previously published, this article adds to the understanding of how and why people search such content. Based on these new insights, we conclude with a discussion of possible design implications for search systems that index micro‐blogging content.